Does the Window of Hope training module for Ghanaian teacher trainees meet the requirements of UNESCO's Technical Guidance on Sexuality Education? - Gordon Yakpir; Juliet Atuguba (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2022)
The Window of Hope (WoH) training Module was introduced in Ghanaian Colleges of Education (CoE) by the Ministry of Education (MoE) to prepare trainees to teach sexuality education upon completion of their training. Using a document analysis methodology, we compared the processes of developing the WoH module and its content to the international technical guidance framework for teacher training on sexuality education. We found that the WoH module is unlikely to achieve its stated objectives as key components of the technical guidance are not catered to in the module. We recommend a comprehensive review of the content of WoH using the National Teacher Preparation Standards Framework  and Ghana's newly developed teacher training standards. We also recommend,  broad consultations involving all interest groups in Ghana in the review process.